Case Report: Proximal duodenal mural mass causing extrahepatic biliary obstruction and reactive pancreatic changes in a dog - Ko, Jae-Yun; Park, Hee-Myung; Kang, Min-Hee (Frontiers in Veterinary Science, 2025)
A 10-year-old castrated male Yorkshire Terrier was referred for acute vomiting and inappetence. Blood tests revealed elevated hepatobiliary and pancreatic enzymes. Ultrasonography identified a hypoechoic mural mass in the cranial duodenum with concurrent dilation of the common bile duct and hypoechoic changes in the pancreas. Fine needle aspiration cytology demonstrated numerous neutrophils without bacteria or neoplastic cells. No pathogens were identified on cytology, histopathology, or culture, raising the possibility of a sterile abscess or a necrotic inflammatory lesion. Computed tomography revealed a well-defined, fluid-attenuating, duodenal mural lesion located near the major duodenal papilla. Surgical exploration and drainage were performed. Histopathology showed marked neutrophilic and macrophagic infiltration in the duodenal muscularis layer. Based on clinical, imaging, and histopathologic findings, the dog was diagnosed with a duodenal mural lesion possibly representing a sterile abscess or necrotic inflammatory mass, associated with extrahepatic biliary obstruction and reactive secondary pancreatitis. Clinical signs improved following surgical treatment, and no recurrence was observed during the two-month follow-up period.